Histopathological Impact of Carica Papaya Seed Extract in Rat Model of Gentamicin Nephrotoxicity - Sameer Ahmed, Mehwish Tayyab, Sher Afghan Khan, M.Aslam Shaikh, Attiya Munir, Amtul Hafeez, Talha Laique, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Kidneys are susceptible to many commonly used drugs, owing to their property of filtering, reabsorbing, and excreting multiple drugs. Aim: To study the renoprotective effect of ethanolic seed extract of Carica papaya on renal histomorphology in nephrotoxicity caused by Gentamicin. Study design: Experimental study. Methodology: Rats (n=30) were subdivided into 3 equal groups. Group I (control group) and Group II & III were administered Gentamicin (80 mg/kg) was given daily for 05 days continuously, intra-peritoneally to cause nephro-toxicity. Histomorphological examination of kidney tissue was done on day-6. In group-III, ethanolic extract of Carica papaya seeds (1000 mg/kg) was given daily for 5 days orally for its induction of nephro-protective effects. Data was entered and analyzed in computer using SPSS. Results: Acute Tubular Necrosis (ATN) and presence of Hyaline casts in the lumen of proximal tubules were the distinctive morphological characteristics. Histopathological specimens of the kidney in Ethanolic treated group showed moderate characteristics of renal damage as compared to that of the disease control group. Conclusion: Study concluded that that Carica papaya seed extract can significantly ameliorate the nephrotoxic effects of Gentamicin thus nephro-protective.